Search, Bargaining, Money, and Prices - Trejos, Alberto; Wright, Randall (Journal of Political Economy, 1995)
This goal of this paper is to extend existing search-theoretic models of fiat money, which until now have assumed that the price level is exogenous, by explicitly incorporating bilateral bargaining. This allows the determination of the price level endogenously and leads to additional insights concerning the role of money. For example, the authors find that monetary equilibria are generally inefficient in the sense that output and prices differ from the solution to a social planner's problem, although the difference can become small as the discount rate or search friction vanishes. The authors also find that there exist nonstationary inflationary equilibria. Copyright 1995 by University of Chicago Press.